Prevalence, characterization and antibiotic resistance of Salmonella spp. isolated from raw vegetables - Mohd Shahril, Najwa (2016)
Growing consumption of fresh vegetables has led to an increase in the number of outbreaks of food-borne disease linked to fresh produce including salmonellosis. In Malaysia, some vegetables are eaten raw, known as ulam or salad in other countries. Therefore, this research was conducted to study the prevalence and antibiotic resistance of Salmonella spp., Salmonella Enteritidis (S. Enteritidis) and Salmonella Typhimurium (S. Typhimurium) in ulam. This study also aimed to determine the relation among different isolates of same serovar of Salmonella spp. by employing random amplification of polymorphic DNApolymerase chain reaction (RAPD-PCR) method and the risk acquiring salmonellosis through consumption of ulam. A total of 96 samples of ulam were purchased from wet markets and hypermarkets in limited geographical locations of Selangor. Most probable number (MPN) method was combined with multiplex polymerase chain reaction (PCR) and plating method for detection of Salmonella spp. Prevalence of Salmonella spp., S. Enteritidis and S. Typhimurium was higher in samples from hypermarkets than wet markets which were 100%, 64.6% and 87.5% respectively at hypermarkets and 95.8%, 43.8% and 75% respectively at wet markets. The density of Salmonella spp., S. Enteritidis and S. Typhimurium ranged from <3 to >2400 MPN/g. MPN-multipex PCR detected more Salmonella spp., S. Enteritidis and S. Typhimurium which were 97.9%, 54.2% and 81.3% respectively, as compared to MPN-plating which were 7.3%, 6.3% and 10.4% respectively. Six isolates of S. Enteritidis and 10 isolates of S. Typhimurium were recovered from ulam. Both Salmonella spp. serovars showed high resistance to amoxicillin/clavunic acid, cephalothin, streptomycin and ciprofloxacin with 100% resistant to ampicillin and erythromycin. All isolates showed resistance to at least three antibiotics tested. S. Typhimurium was more resistant compared to S. Enteritidis with multiple antibiotic resistances (MAR) index ranging from 0.27 to 0.82 and 0.27 to 0.55 respectively. RAPD-PCR dendograms showed that most isolates of S. Enteritidis and S. Typhimurium tend to type together based on same sample type which 3 RAPD types (RAPD type 3 of S. Enteritidis and RAPD type 1 and 6 of S. Typhimurium) were typed together respectively on same sample type and same sampling locations. The other 3 RAPD types (RAPD type 1 of S. Enteritidis, RAPD type 2 and 4 of S. Typhimurium) were typed based on the same sample type but different sampling locations. RAPD type 3 of S. Typhimurium was typed on different sample types but same sampling location was observed. The quantitative microbiological risk assessment (QMRA) simulations by single-hit concept showed that overall risk of acquiring salmonellosis due to consumption of ulam was higher for S. Typhimurium than S. Enteritidis. The mean risk of illness per serving per year for S. Typhimurium was 1 while for S. Enteritidis, the risk was ~1 in the exposed population. All in all, the prevalence of Salmonella spp. in ulam is alarming and should be monitored from time to time seems prevention is better than cure.